Rola i znaczenie mediów w kształtowaniu obrazu polsko-niemieckiego pogranicza w latach 90. XX wieku (na przykładzie „Gazety Pogranicza” – dodatku do „Gazety Wyborczej”) - Olechowska, Paulina (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2015)
The article is an attempt to determine the role of the media in shaping the image of the Polish- German borderlands. As examples, press releases published (from August 1994 to November 1996) in Gazeta Pogranicza [Borderland Gazette] were used. The newspaper is the result of cooperation between local editorial supplements to Gazeta Wyborcza and the Brandenburg regional daily newspaper Märkische Oderzeitung. An important element of this research is the assumption that the foundation of any international communication is the need to know and understand.